Analisis Pengaruh Pembelajaran Berbasis Proyek terhadap Kemampuan Komunikasi Siswa Sekolah - Yulianti, Euis; Cancer, Julius (Papanda Publisher, 2022)
This study investigates the effect of project-based learning on students' communication skills at SDN Wanasalam I. The research methods employed include observation, interviews, and document analysis. The subjects of the study were elementary school students at SDN Wanasalam I, who were involved in project-based learning during the research period. The results of the study indicate a significant improvement in students' communication skills after participating in project-based learning. Observations reveal an increase in student participation in classroom discussions, while interviews confirm an enhanced level of confidence among students in speaking in public. Document analysis shows an improvement in the quality of students' learning products, such as project reports and presentations. The conclusion affirms that project-based learning is effective in enhancing students' communication skills in elementary school. The practical implications of this research underscore the importance of considering communication skills in curriculum design and teaching practices at the elementary school level. Therefore, it is recommended for educational practitioners to integrate project-based learning into elementary school curricula as a comprehensive approach to improving students' communication skills.